Benefits of Developing E-Commerce Platform for Informatics Students as Additional Income - Natalia Artha Malau; Michelle Sihombing; Jovial Rembang; Hendra Gusasi; Gabriel Patras; Fareeld Rumengan (Syntax Corporation Indonesia, 2024)
The article in this journal will bring readers more specifically to university students to see easier access to money for additional living expenses. A new perspective when students are more specifically informatics students who are taught and nurtured so that they have skills and knowledge about program development not only live with money given by parents, but with money from the creation and development of their own programs or platforms. Access and dissemination of this journal will be expanded to make it more accessible and useful to all readers not only for informatics students but for prospective students and former students who have dived into the sea of computer code more specifically on the creation and development of programs or platforms.